PENGARUH VARIASI LARUTAN pH BUFFER TERHADAP KARAKTERISTIK EKSTRAK ALGA MERAH (Gracilaria sp.) SEBAGAI PEWARNA - Sinaga, Esra Palenta; Suhendra, Lutfi; Ganda Putra, G. P. (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2019)
Gracilaria sp. is one type of red algae containing phycoerytrin pigment. Phycoerytrin pigment can be used as a natural dye to replace synthesis dyes. Phycoerytrin is widely used as a natural dye for foods and cosmetics. The purpose of this research was 1) to determine the effect of variations pH buffer solution on the characteristics of red algae extract (Gracilaria sp.), 2) to determine the best pH buffer solution used to produce red algae extract (Gracilaria sp.). This study used a factorial Randomized Block Design with group variation of pH buffer. The treatment of materials with solvent variation of pH buffer consist of 8 level, namely: 3, 4, 5, 6, 7, 8, 9 and 10. Each treatment are grouped into two time-based implementation. The results showed that each treatment of pH buffer variation significantly affected the yield, the degree of phycoerytrin pigment, brightness (L *), redness (a *) and yellowish (b *). Buffer pH 7 produced the best extracts in red algae (Gracilaria sp.) with a yield of 0.6030%, pigment production 0.933 mg/g, brightness value 18.650 L *, redness value 24.470 a * and yellowish value 10.135 b *. Keywords: Gracilaria sp., phycoerytrin, pH Buffer, extract characteristic.